Gurindam Dua Belas Contribution Composition Raja Ali Haji (1808 – 1873 M) in Enriching the Treasures of Islam - Nurliana Nurliana; Miftah Ulya; Sukiyat Sukiyat; Usman Usman (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
Abstract: Gurindam Dua Belas Composition Raja Ali Haji part of the ancient manuscripts of the pride of the Riau Malay people and the Riau Archipelago, Gurindam contains a unique message consisting of twelve chapters, Each chapter contains advice that is in line with the order of human life, the first article is a message of religious advice, ending in the article the twelfth about the message before facing death. Gurindam is a unique culture in the form of artistically valuable literature which is sung in Malay rhythms at traditional events in the Malay area which are enshrined by the people, especially the Riau Malays and the Riau Islands. Gurindam Dua Belas contains its own meaning attached to its people so that its existence exists to this day. The research method used by library research is content analysis. The research findings show that the contribution of Gurindam Dua Belas in Islamic literature is literature with artistic value, messages of religious advice, messages of education, moral messages, messages of order of life. Keyword: contribution, gurindam, treasure, Islam